4 - Investment in Security Forces and Human Development Challenges in Africa: Lessons from Nigeria’s Experience - Suchi, Plangshak Musa (Africa Development, 2019)
This article addresses the question of how investment in state security forces has affected the capacity and interest of African states to deal with other human development challenges, using Nigeria as its empirical core. In particular, the Nigerian state’s response to contemporary security challenges in the country, such as insurgency and terrorism, kidnapping, and herders–farmers conflicts, provides the basis for the discussion. Based on secondary data analysis, the article argues that enormous resources have been invested in security forces in Nigeria since independence in 1960, at the expense of fixing other basic human development challenges such as widespread misery and poverty, poor healthcare facilities, low life expectancy, low literacy, high levels of unemployment, and monumental corruption especially among high profile individuals, organisations and governments. The article emphasises the cost of counter-insurgency in terms of huge budgetary allocations to the security forces, especially how this has crowded out resources from other human development challenges in the country.